PENGARUH MOTIVASI, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN POLITEKNIK SWASTA DI BANDUNG - Dematria Pringgabayu; Nur Azizah; Hendriady de Keizer (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The purpose of this study to determine: 1) Motivation, Competence, Work Environment and Performance of Employees in Private-owned Politechnic; 2) to determine the effect of motivation on Employee Performance, 3) to determine the effect of Competence on employee performance; 4) to determine the effect of Work Environment Employee Performance; 5) to determine the effect of Motivation, Competence and the Work Environment simultaneously on Employee Performance Politeknik Pajajaran Insan Cinta Bangsa Bandung. The method is a method of research used census (population) of 35 respondents using descriptive analysis and verifikatif. From the results of descriptive analysis showed that the total effect of motivation (X1) of the Employee Performance (Y) of 63.3%, the total effect of Competency (X2) of the Employee Performance (Y) of 14.8%, and the total effect of Work Environment (X3) Performance of Employees (Y) of 7.7%. While the influence of Competence, Motivation, Corporate Culture of Performance jointly or simultaneously have the effect of a total of 85.8%.